Stormbringers - Gregory, Philippa (London : Simon and Schuster, 2013)
Luca and Isolde continue their journey searching for evil in medieval Christendom.
Keywords: Adventure stories; Paranormal fiction; Secret societies -- Juvenile fiction; Church history -- Juvenile fiction; Young adult fiction